The Application of Wearable Technology in Surgery: Ensuring the Positive Impact of the Wearable Revolution on Surgical Patients - Slade Shantz, Jesse Alan; Veillette, Christian J. H. (Frontiers in Surgery, 2014)
Wearable technology has become an important trend in consumer electronics in the past year. The miniaturization and mass production of myriad sensors has made possible the integration of sensors and output devices in wearable platforms. Despite the consumer focus of the wearable revolution some surgical applications are being developed. These fall into augmentative, assistive and assessment functions and primarily layer onto current surgical workflows. Some challenges to the adoption of wearable technologies are discussed and a conceptual framework for understanding the potential of wearable technology to revolutionize surgical practice are presented.